Polymers for Combating Biocorrosion - Guo, Jing; Yuan, Shaojun; Jiang, Wei; Lv, Li; Liang, Bin; Pehkonen, Simo O. (Frontiers in Materials, 2018)
Biocorrosion has been considered as big trouble in many industries and marine environments due to causing great economic loss. The main disadvantages of present approaches to prevent corrosion include being limited by environmental factors, being expensive, inapplicable to field, and sometimes inefficient. Studies show that polymer coatings with anti-corrosion and anti-microbial properties have been widely accepted as a novel and effective approach to preventbiocorrosion. The main purpose of this review is to summarize up the progressive status of polymer coatings used for combating microbially-induced corrosion. Polymers used to synthesize protective coatings are generally divided into three categories: i) traditional polymers incorporated with biocides, ii) antibacterial polymers containing quaternary ammonium compounds, and iii) conductive polymers. The strategies to synthesize polymer coatings resort mainly to grafting anti-bacterial polymers from the metal substrate surface using novel surface-functionalization approaches, such as free radical polymerization, chemically oxidative polymerization and surface-initiated atom transfer radical polymerization, as opposed to the traditional approaches of dip coating or spin coating.